Description of a new Psychoda Latreille species from Fennoscandia (Diptera: Psychodidae) - Salmela, Jukka; Kvifte, Gunnar M.; More, Anna (Zootaxa, 2012)
Psychoda cultella sp. n. is described. The new species is characterized by 16-segmented antennae with the three apicalflagellomeres globular, very short and partially fused; labellum with five terminal digital projections; aedeagus ca 1.7times the length of gonostylus; distiphallus bipartite, composed of a ventral phallomere with a roundish blunt tip and adorsal phallomere with pointed tip; basiphallus in lateral view sub-basally widened. The new species is known from Fin-land (29 localities) and Norway (6 localities), ranging from the southern boreal ecoregion to the subalpine zone. Psychodacultella sp. n. is mainly found in Malaise trap samples collected from moist coniferous forests and spruce mires (riparianforests, springs) and rarely from fens and subalpine heaths. Two male specimens from Norway were reared from fruiting bodies of polypore fungi (either Fomes fomentarius or Piptoporus betulinus).